2019
DOI: 10.3390/ijms20020268
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin Enhances the Chemosensitivity of Cancer Cells to ABCB1 Substrates

Abstract: ABCB1 is one of the major drug efflux transporters that is known to cause multidrug resistance (MDR) in cancer patients receiving chemotherapy for the treatment of solid tumors and hematological malignancies. Inhibition of ABCB1 efflux function is important for maintaining the intracellular concentration of chemotherapeutic drugs. Here, we evaluated ciprofloxacin for its ability to reverse MDR caused by the overexpression of ABCB1. Cytotoxicity of ciprofloxacin was determined by the MTT assay. The chemosensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Furthermore, it is likely that the effects of quinazoline-based EGFR inhibitors, including sapitinib, on ABC transporters, are due to their structures, indicating that certain structures inhibit the efflux function of ABC transporters. However, we cannot rule out the possibility that the increase in anticancer drug efficacy produced by sapitinib could be due to its inhibition of tyrosine kinases ( 52 , 53 ). Finally, sapitinib did not significantly alter the cytotoxic efficacy of cisplatin and oxaliplatin, two anti-cancer drugs that are not substrates for the ABCB1 transporter ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is likely that the effects of quinazoline-based EGFR inhibitors, including sapitinib, on ABC transporters, are due to their structures, indicating that certain structures inhibit the efflux function of ABC transporters. However, we cannot rule out the possibility that the increase in anticancer drug efficacy produced by sapitinib could be due to its inhibition of tyrosine kinases ( 52 , 53 ). Finally, sapitinib did not significantly alter the cytotoxic efficacy of cisplatin and oxaliplatin, two anti-cancer drugs that are not substrates for the ABCB1 transporter ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ABCB1 (P-gp, MDR1) and ABCG2 (breast cancer resistance protein, BCRP) have been identified as the major contributor to MDR in variety of cancers (3,(9)(10)(11). Many studies suggested that the overexpression of ABCB1 and ABCG2 cause reduction of intracellular drugs (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Beside the development of special P-gp regulators, drug repurposing has emerged as another appealing strategy as those molecules have been assessed in clinical/preclinical trials and considered as safe enough [36,37]. Many small molecular drugs, including TKIs [38], phosphodiesterase inhibitors [39], and fluoroquinolone antibiotics [40], antagonize P-gp mediated MDR at non-cytotoxic concentrations. These studies provide important information for future clinical trials and for further new drugs targeting P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…MK-8776 exhibited similar effects to these three drugs in HEK293/ ABCB1 cells, which are normal cell lines that were transfected with ABCB1 ; meanwhile, it exhibited no such effects to the non-Pgp substrate cisplatin, indicating its effects in modulating P-gp functions. As we can observe, since all cells expressed a high level of P-gp [40], the RF of the chemotherapeutics and the reversal effects by MK-8776 in KB-C2 or SW620/Ad300 cells and HEK293/ ABCB1 cells were different. The RF in KB-C2 or SW620/Ad300 cells were higher than in HEK293/ ABCB1 cells, and the reversal effects of MK-8776 and verapamil in KB-C2 or SW620/Ad300 cells were weaker than in HEK293/ ABCB1 cells.…”
Section: Discussionmentioning
confidence: 99%